Pengaruh Quality of Work Life dan Internalisasi Kode Etik Terhadap Pengambilan Keputusan Restorative Justice Kasus Penyalahgunaan Narkoba : Studi di Satuan Narkoba Polresta Sidoarjo - Laksono, Tidar; Prisgunanto, Ilham; Sudarto, Eko Rudi (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2024)
Law and humanism are inherently intertwined and inseparable in handling cases of drug abuse. Drug abusers are divided into self-abusers, victims of drug abuse, and drug addicts who do not report. Punishment for those involved in drug abuse is criminal punishment. The aim of this study is to analyze the simultaneous influence of Quality of Work Life (QWL) and the internalization of police code of ethics on the decision-making of restorative justice for drug abuse. This research is observational. The research variables are quality of work life (QWL), internalization of professional code of ethics, decision-making in restorative justice cases of drug abuse. The population is the community of Bangkalan with a sample size of 51 people taken using total sampling technique. Data collection tools use questionnaires and are analyzed using regression. Quality of Work Life (QWL) and internalization of police code of ethics simultaneously influence decision-making in restorative justice for drug abuse. The stronger the Internalization of Professional Code of Ethics together with QWL, the fairer the decision-making in restorative justice for drug abuse.